Genetic structure and barcode identification of an endangered orchid species, Liparis loeselii, in Poland. Issue 4 (3rd July 2016) - Wiland-szymańska, Justyna; Buczkowska, Katarzyna; Drapikowska, Maria; Maślak, Magdalena; Bączkiewicz, Alina; Czylok, Andrzej
Abstract : The genetic diversity of five populations of Liparis loeselii from two regions of Poland, Podlachia and Silesia, was compared with respect to minisatellite markers. Moreover, the standard 2-loci barcode DNA regions, rbcL and matK genes, as well as an additional region trnL-F from chloroplast and ITS2 from nuclear genome were studied. The total genetic diversity at the species level amounted to H T = 0.356. The analysis of molecular variance revealed that 58% of genetic variation was distributed within populations, 2% among populations, and 40% between regions from NE Poland (Podlachia), and S Poland (Silesia). Nei's genetic distances indicated that specimens from the Podlachia population were genetically isolated from Silesian ones. Two genetic barriers among the studied populations were found: one barrier separated the Podlachian population from all Silesian populations and another barrier divided Kuźnica Warężyńska population from other Silesian populations. Based on barcode sequences it was found that all the examined samples were identical with respect to all the studied DNA regions. Liparis loeselii trnL-F region sequences were detected for the first time and they can be useful as complementary barcodes for this species. The analysed sequences of L. loeselii are fully consistent with sequences of specimens originating from the UK, Canada, Czech Republic, Hungary, Sweden, Italy, and Russia.